Nutritional status and diabetes knowledge as predictors of healthy lifestyle behaviors for prediabetes prevention in adolescents - Nur Indah Noviyanti; Reza Bintangdari Johan; Rusmiati Rusmiati; Cici Ismuniar; Ruqaiyah Ruqaiyah; Hukmiyah Aspar; Rahmi Padlillah (Intelektual Pustaka Media Utama, 2026)
Prediabetes prevalence among adolescents has increased substantially worldwide, with estimates indicating that approximately 18-20% of adolescents in certain populations exhibit impaired glucose metabolism, paralleling the global rise in adolescent obesity. In Indonesia, the prevalence of diabetes mellitus continues to escalate, with North Kalimantan representing an underserved region where adolescent metabolic health remains poorly characterized. Identifying modifiable factors associated with prediabetes prevention behavior is essential for developing targeted interventions. To analyze factors associated with prediabetes prevention behavior in adolescents, focusing on nutritional status and knowledge about diabetes mellitus. A cross-sectional analytical design was employed among 316 adolescents aged 13-15 years in Tarakan City, North Kalimantan, Indonesia, selected through proportional stratified random sampling. Data were collected using a demographic questionnaire, an adapted diabetes knowledge questionnaire (DKQ-24), and a prediabetes prevention behavior questionnaire. Chi-square tests and binary logistic regression were performed. Most respondents (53.2%) demonstrated positive prevention behavior, and 70.9% had high knowledge. Nutritional status (p = 0.000) and knowledge (p = 0.033) were significantly associated with prevention behavior. Multivariate analysis confirmed nutritional status (Exp(B) = 1.320; 95% CI: 1.017-1.714) and knowledge (Exp(B) = 0.583; 95% CI: 0.352-0.965) as significant predictors (Nagelkerke R² = 0.052). Nutritional status and diabetes knowledge significantly predict prediabetes prevention behavior, although their contributions remain relatively small.